Management of infection prophylaxis in Dutch patients with myelodysplastic syndromes, a web‐based case vignette questionnaire: The MINDSET study. (6th July 2022) - Rozema, Johanne; van Roon, Eric; Vogelzang, Lars; Kibbelaar, Robby; Veeger, Nic; van de Loosdrecht, Arjan; Hoogendoorn, Mels
Abstract: Objectives: Infections are a major cause of morbidity and mortality in patients with myelodysplastic syndromes (MDS). The objective of the MINDSET study was to evaluate haematologists' management of infection prevention in MDS patients using a case vignette study and to assess the availability of guidelines. Methods: We conducted a web‐based, nationwide survey amongst haematologists in the Netherlands between September and December 2021. The survey included a set of case vignettes. In addition, the availability of protocols was evaluated. Results: Sixty responses were obtained (23.6%). These responses were well distributed across hospital types as well as level of experience. No protocols regarding infection prophylaxis specifically for MDS patients were received. In the case vignette of a 75‐year‐old MDS patient, respondents would primarily prescribe infection prophylaxis in case of recurrent infections (96.7%) and neutropenia (75.0% for absolute neutrophil count [ANC] < 0.2 × 10 9 /L and 53.3% for ANC < 0.5 × 10 9 /L), especially in combination with hypomethylating agents (80.0%), lenalidomide (66.7%) or chemotherapy (51.7%). Respondents would predominantly choose antibacterial agents (85.0%), followed by antifungal agents (71.7%). Conclusions: This study showed diverse reasons and considerations of haematologists regarding whether to prescribe infection prophylaxis in MDS patients. Given the seriousness of infections in MDS patients, patient‐tailored recommendations might be valuable in clinical decision‐making.